Aplicación de la fundamentación técnica del fútbol en los procesos de iniciación deportiva en los niños de la categoría sub 8 de la liga deportiva parroquial Mulalo. - Chancusig Viracucha, Teodoro Cristóbal (2019)
The purpose of this research was to highlight league Mulaló parish reality where the analysis was based on soccer technical foundations work and how these will contribute to the sports initiation processes in sub 8 children category. This research topic talks about the development of each soccer technical foundations where is can determined on: Driving, passing, receiving, dominating, dribbling, pitching, finishing. Through they will contribute to sport initiation processes, consequentlly to form the child in a sportive game and recreation area, this means that it satisfies their needs according to the activity that they use and they can develop independently at the society. This document applies a descriptive research with a non-experimental designing, based on a fieldwork, using the statistical method with the survey technique and its instrument the questionnaire to collect information about the facts referring to technical learning foundations of soccer and how they will contribute on sports initiation children processes of Mulaló soccer school. Finally, it was concluded that the process of this research will contribute significantly to the development of children who belong to this training school, not only in the sports area but also in their integral training.